The taletellers in Malay society: the Penglipur Lara of Batu Pahat - Abu Bakar, Roslina; Wessels, Joosje (Cambridge Scholars Publishing, 2024)
The aim of this article is not to analyse or to give a deeper insight into the subtle workings of the penglipur lara‘s art, but rather to give some examples that showcase the versatility of their performances, the context in which they occur, and to briefly describe their role in the Malay society of Batu Pahat. The examples were all gathered across the district during the final months of 2004 and the starting months of 2005. The data consists of four recordings, in turn consisting of two performances and two interviews. Mr. Ali Badron Bin Haji Sabor was the main participating penglipur lara, who shared his knowledge during and after his performances.